2023
DOI: 10.1021/acs.jafc.3c01023
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 as a Valuable Tool for Aroma Technology

Abstract: This review addresses the possibilities of using supercritical carbon dioxide (SC-CO2) in the flavor industry in extraction and fractionation processes and its use as a reaction medium to generate aroma esters. The advantages and disadvantages are presented, comparing SC-CO2 processing with traditional methods. The most distinguishable features of SC-CO2 include mild reaction conditions, time savings, fewer toxicity concerns, higher sustainability, and the possibility of modulating solvent selectivity accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…By recognizing the value inherent in the leaves and flowers of Białobrzeskie, Henola, and Tygra, and their potential biological activity, we can maximize the benefits derived from these hemp varieties, enhancing both agricultural practices and human health on multiple fronts. scCO 2 is a commonly used extractant in the pharmaceutical and natural products industries [69][70][71][72][73]. It is a non-toxic, non-flammable, and environmentally friendly solvent [74,75], and it can be easily removed by depressurization and evaporation [76][77][78].…”
Section: Extractionmentioning
confidence: 99%
“…By recognizing the value inherent in the leaves and flowers of Białobrzeskie, Henola, and Tygra, and their potential biological activity, we can maximize the benefits derived from these hemp varieties, enhancing both agricultural practices and human health on multiple fronts. scCO 2 is a commonly used extractant in the pharmaceutical and natural products industries [69][70][71][72][73]. It is a non-toxic, non-flammable, and environmentally friendly solvent [74,75], and it can be easily removed by depressurization and evaporation [76][77][78].…”
Section: Extractionmentioning
confidence: 99%
“…10 Another alluring option for the downstream procession of flavor compounds is discussed in the review-type paper "Supercritical CO 2 as a Valuable Tool for Aroma Technology" by Rafael Moreiraa et al The review illustrates the possibilities of supercritical carbon dioxide in the flavor industry in extraction and fractionation processes, but also in its use as a reaction medium to generate aroma esters. 11 The session "Olfaction and taste perception" was introduced by Maarten Jongsma with his keynote lecture "Tongue on a chip -a microfluidic application of receptomics", which gave a fascinating overview on the microfluidic receptomics platform (www.receptomics.com) developed by his group. It represents a "tongue-on-a chip" application that allows for the detection of activation patterns of the bitter, umami, and sweet taste receptors by liquid food or food extracts.…”
Section: Conference Sessionsmentioning
confidence: 99%
“…Another alluring option for the downstream procession of flavor compounds is discussed in the review-type paper “Supercritical CO 2 as a Valuable Tool for Aroma Technology” by Rafael Moreiraa et al The review illustrates the possibilities of supercritical carbon dioxide in the flavor industry in extraction and fractionation processes, but also in its use as a reaction medium to generate aroma esters …”
Section: Selected Contributions From the Specific Conference Sessionsmentioning
confidence: 99%
“…For supercritical fluid extraction, environmental benefits such as operation without hazardous organic solvents and usage of non-flammable CO2 as a solvent are the major strong points, while the high instrument cost and high-pressure operation are the drawbacks of this technique [10]. It has been reported that the extracted lipid from rambutan seeds is a promising unconventional source of specialty fat for the cosmetic and personal care industries because it contains oleic and arachidic acids as the major fatty acids [11].…”
Section: Introductionmentioning
confidence: 99%